(K, Na, Li)(Nb, Ta)O3:Mn Lead‐Free Single Crystal with High Piezoelectric Properties. Issue 6 (17th March 2015) - Huo, Xiaoqing; Zhang, Rui; Zheng, Limei; Zhang, Shujun; Wang, Rui; Wang, Junjun; Sang, Shijing; Yang, Bin; Cao, Wenwu; Lupascu, D.
<x xml:space="preserve">Abstract</x> Lead‐free single crystal, (K, Na, Li)(Nb, Ta)O3:Mn, was successfully grown using top‐seeded solution growth method. Complete matrix of dielectric, piezoelectric, and elastic constants for [001]C poled single crystal was determined. The piezoelectric coefficient d33 measured by the resonance method was 545 pC/N, which is almost three times that of its ceramic counterpart. The values measured by the Berlincourt meter (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjrk68wf0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />d33∗</alternatives> = 630 pC/N) and strain–field curve (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjrk68wdg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />d33∗∗</alternatives> = 870 pm/V) were even higher. The differences were assumed to relate with the different extrinsic contributions of domain wall vibration and domain wall translation during the measurements by different approaches, where the intrinsic contribution (on the order of 539 pm/V) was supposed to be the same. The crystal has ultrahigh electromechanical coupling factor (k33 95%) and high ultrasound velocity, which make it promising for high‐frequency medical transducer applications.